Reparable Harm Assessing and Addressing Disparities Faced by Boys and Men of Color in California, Executive Summary - Davis, Lois M. (RAND Corporation, 2009)
The summary discusses some of the greatest disparities for boys and men of color relative to their white counterparts across specific socioeconomic, health, safety, and school readiness indicators in California and provides information about different strategies for reducing the disparities--including effective programs, practices, and policies--that can begin making an important difference in changing the life course of boys and men of color.